Tráfico ilícito de bens culturais e a evasão do patrimônio bibliográfico e arquivístico brasileiro: o caso do furto à Coleção de Obras Raras do Museu Paraense Emílio Goeldi - (:unkn) unknown (Museu Paraense Emílio Goeldi, 2021)
The article addresses the illicit trafficking of elements from Brazil’s bibliographic and archival heritage. It begins with a normative approach to the topic, and then draws an overview of the cases of theft and robbery of rare printed and manuscript materials that have taken place in Brazilian institutions from the beginning of the 21st century onwards. A proposal is made to investigate how the theft in the Special Collection of the Library of the Emilio Goeldi Museum of Pará [Museu Paraense Emílio Goeldi], in 2008, is connected to other facts reported in the country. The sources used in the article are of bibliographic and archival nature. The records of the legal proceedings concerning the case were consulted for its analysis. The article concludes that there are connecting elements between the theft in Goeldi Museum and other crimes against heritage institutions recorded in the country. Concerning the methodological approach, this research is classified as descriptive, exploratory, and qualitative.
Illicit trafficking of cultural property and the dispersion of the Brazilian bibliographic and archival heritage: the case of theft to the Collection of Rare Works of the Emilio Goeldi Museum of Pará
Keywords: Tráfico ilícito de bens culturais; Patrimônio bibliográfico; Patrimônio arquivístico; Obras raras; Furto; CNPQ::CIENCIAS SOCIAIS APLICADAS::COMUNICACAO